A co-delivery platform for synergistic promotion of angiogenesis based on biodegradable, therapeutic and self-reporting luminescent porous silicon microparticles. (May 2021) - Duan, Wei; Jin, Yao; Cui, Yaoxuan; Xi, Fengna; Liu, Xingyue; Wo, Fangjie; Wu, Jianmin
Abstract: Insufficient angiogenesis happened in body defects such as ulceration, coronary heart disease, and chronic wounds constitutes a major challenge in tissue regeneration engineering. Owing to the poor bioactivity and maintenance of pro-angiogenic cells and factors during transplantation, new bioactive materials to tackle the barrier are highly desirable. Herein, we demonstrate a co-delivery platform for synergistic promotion of angiogenesis based on biodegradable, therapeutic, and self-reporting luminescent porous silicon (PSi) microparticles. The biodegradable and biocompatible PSi microparticles could quickly release therapeutic Si ions, which is bioactive to promote cell migration, tube formation, and angiogenic gene expression in vitro . To construct a highly efficient angiogenesis treatment platform, vascular endothelial growth factor (VEGF) was electrostatically adsorbed by PSi microparticles for effective drug loading and delivery. The dual therapeutic components (Si ions and VEGF) could release with the dissolution of Si skeleton, accompanying by the decay of photoluminescence (PL) intensity and blue shift of the maximum PL wavelength. Therefore, real-time drug release could be self-reported and assessed with the two-dimensional PL signal. The co-delivery of Si ions and VEGF displayed synergistic effect and highly efficient angiogenesis, which was evidenced by the enhancement of endothelial cell migration and tube formation in vitro with approximately 1.5–5 times higher than control. The blood vessel formation in vivo was also significantly improved as shown by the chick chorioallantoic membrane (CAM) model, in which the total length, size and junctions exhibited 2.1 ± 0.4, 4 ± 0.4, and 3.9 ± 0.3 times in comparison to control, respectively. The PSi and VEGF co-delivery system display great potential in tissue engineering as a biodegradable and self-reporting theranostic platform to promote angiogenesis. Graphical abstract: Image 1